Peningkatan Hasil Belajar Geometri Peserta Didik dengan Menggunakan Model Student Teams Achievement Division (STAD) di Kelas IV SDN 05 Birugo Kota Bukittinggi - Azizah, Putri; Helsa, Yullys (Darul Yasin Al Sys, 2025)
This study was prompted by the low academic performance of students, which was attributed to inadequate lesson planning by the teacher, suboptimal implementation of instructional activities, and limited active student participation in the learning process. The aim of this research is to describe the improvement in student learning outcomes in geometry through the implementation of the Student Teams Achievement Division (STAD) model in Grade IV at SDN 05 Birugo, Bukittinggi. This study employed a classroom action research (CAR) design, incorporating both quantitative and qualitative approaches, and was conducted with 18 fourth-grade students. The research was implemented in two cycles: Cycle I consisted of two sessions, and Cycle II comprised one session. Each cycle followed four stages—planning, implementation, observation, and reflection. The findings of the study indicated significant improvements in several aspects: a) The quality of the teaching module improved from 83.3% (good) in Cycle I, Session I to 87.5% (good) in Cycle I, Session II, and reached 95.83% (very good) in Cycle II; b) The teacher's instructional performance increased from 78.13% (fair) in Cycle I, Session I to 87.5% (good) in Cycle I, Session II, and 93.75% (very good) in Cycle II; c) Student participation rose from 71.87% (fair) in Cycle I, Session I to 81.25% (good) in Cycle I, Session II, and 93.75% (very good) in Cycle II; d) Student learning outcomes increased from an average score of 74 (fair) in Cycle I, Session I to 82.9 (good) in Cycle I, Session II, and 90.7 (very good) in Cycle II. In conclusion, the implementation of the STAD learning model effectively enhanced student learning outcomes in geometry among Grade IV students at SDN 05 Birugo, Bukittinggi.